How to write a great school report - James, Elizabeth; Barkin, Carol (New York : Lothrop, 1983)
Explains how to choose a topic for a report, how to find and organize information, and how to write and revise the final version.
Includes index.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
School Library Journal.
7.4
7.4
Keywords: Report writing -- Juvenile literature; English language -- Composition and exercises; Homework; Report writing; Research; English language; Report writing; Research